Ribonucleosides, Aminoacyl- and Peptidyl-RNA: Synthesis, Thermodynamics, and Structure - Ewa Biala; Oliver Botta; Elisabeth Moyroud; Peter Strazewski (CHIMIA)
Ribonucleosides, RNA and peptides are prepared to study non-covalent interactions of RNA, aminoacyl- and peptidyl-RNA. Techniques used include chemical synthesis in solution and on solid supports, UV- and NM-detected thermal denaturation, X-ray crystallography and 1H-NMR spectroscopy for conformational studies, assisted by force-field and ab initio calculations.